The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000491804
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Synapsis and Gene Expression Altered by a Balanced Y-Autosome Reciprocal Translocation in an Azoospermic Pig

Abstract: Meiotic sex chromosome silencing (MSCS) has been argued as a prerequisite for normal meiotic cell division progression during the synaptic prophase I stage. Furthermore, irregular asynapsis of autosomal axes at meiosis may be encompassing the lack of transcriptional activity normally observed for the X and Y sex chromosomes. Therefore, any chromosomal rearrangement compromising the normal mechanism of MSCS and/or the contrary, the normal meiotic transcriptional activity of autosomal chromosomes, may be observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Thus, in the system studied by Turner et al the X silencing occurs in about 50% of synapsed X chromosome regions. Similarly, Mary et al reported that in a boar with translocation of chromosomes 13 and Y, about 50% of the Y and X chromosomes showed no γH2AX signal in pachytene spermatocytes nuclei 38 . Similar levels were reported by Barasc et al in a boar with translocation of chromosomes 1 and Y 35 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, in the system studied by Turner et al the X silencing occurs in about 50% of synapsed X chromosome regions. Similarly, Mary et al reported that in a boar with translocation of chromosomes 13 and Y, about 50% of the Y and X chromosomes showed no γH2AX signal in pachytene spermatocytes nuclei 38 . Similar levels were reported by Barasc et al in a boar with translocation of chromosomes 1 and Y 35 .…”
Section: Discussionmentioning
confidence: 86%
“…Previous reports indicated that MSCI is disrupted in heterogametic cells with sex-chromosome to autosome translocations and that, in some cases, gene expression was uncoupled from the synapsis state of the translocated chromosomes 30, 34, 35, 37, 38 . This suggested that disruption of chromosome integrity prevents initiation of MSCI.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, while Y-autosome translocations involve different and nonhomologous autosomes in different species, a common denominator for all cases is the involvement of the Y chromosome. Therefore, and as shown by several studies [3][4][5]17,36], a more plausible explanation for meiotic arrest is the failure to properly inactivate sex chromosomes, particularly the Y chromosome. This is in line with a recently presented theory about "the persistent Y" and "meiotic executioner genes" [37].…”
Section: Discussionmentioning
confidence: 93%
“…In the general human population, based on a study of 11,148 newborn infants, the incidence of Y-autosome translocations is approximately 1/2000 [ 1 ]. In domestic animals, five cases have been reported in pigs [ 2 , 3 , 4 , 5 ], two cases in cattle [ 6 , 7 ], and one case in horses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The meiotic behavior of chromosomal rearrangements has been investigated in a limited number of cases in pigs. Indeed, until now, meiotic analyses concerned only three Y-autosome [35,38,39] and one autosome-autosome translocations in this species [31]. Yautosome translocations lead to an association of autosomes with the XY body, resulting in a total arrest of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%